2018
DOI: 10.1111/cei.13132
|View full text |Cite
|
Sign up to set email alerts
|

PR-957 mediates neuroprotection by inhibiting Th17 differentiation and modulating cytokine production in a mouse model of ischaemic stroke

Abstract: Acute ischaemic stroke can induce secondary brain injury by activating an inflammatory response that contributes to clinical impairment. As a specific inhibitor of the immunoproteasome subunit low molecular weight polypeptide 7 (LMP7), PR-957 may participate in regulating pathophysiological and inflammatory responses in multiple diseases of the central nervous system (CNS). We investigated the neuroprotective properties of PR-957 in a mouse model of stroke, induced by middle cerebral artery occlusion (MCAO). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…Studies have demonstrated IL-6 plays a prominent role in regulating the balance between Th17 cells and regulatory T cells [ 56 ], which affects inflammation. Inhibiting T lymphocyte infiltration and decreasing Th17 cells differentiation could provide neuroprotection of ischemic stroke [ 57 ]. It was also reported that IL-6 produced by mature adipocytes and fibroblast supports breast tumor growth and metastasis [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated IL-6 plays a prominent role in regulating the balance between Th17 cells and regulatory T cells [ 56 ], which affects inflammation. Inhibiting T lymphocyte infiltration and decreasing Th17 cells differentiation could provide neuroprotection of ischemic stroke [ 57 ]. It was also reported that IL-6 produced by mature adipocytes and fibroblast supports breast tumor growth and metastasis [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an excessive activity of immunoproteasomes may contribute to Th17/Treg disequilibrium in IgAN. It has been evidenced that immunoproteasome subunit coded by PSMB8 gene is necessary for Th17 differentiation and inhibits Treg differentiation [41, 42]. It was demonstrated that PBMC of IgAN patients had higher expression of PSMB8 gene [43, 44], especially those individuals with high proteinuria [43] or those experiencing greater annual loss of eGFR [45].…”
Section: Alterations Of T Cell Subpopulations In Iga Nephropathymentioning
confidence: 99%
“…Furthermore, IP inhibition in preclinical animal models protected from colitis-associated cancer formation (18,19) exacerbated the pathogenesis of experimental systemic Candida albicans infection (20), protected from virus-induced myocarditis (21), and prevented organ rejection in transplantation (22)(23)(24). Two major pathways involved in disease development are affected by LMP7 inhibition, namely Th cell differentiation (15,(25)(26)(27)(28) and cytokine secretion (13,25,27,29,30). The LMP7/ LMP2-specific inhibitor ONX 0914 (25,31) strongly reduced the secretion of different proinflammatory cytokines of TCR-activated T cells and endotoxin-stimulated human PBMCs or mouse splenocytes (20,25,(29)(30)(31).…”
mentioning
confidence: 99%